(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In primary teacher education programs, one of the most important outcomes is the formation of favorable attitudes about teaching. Future teachers’ motivation, instructional conduct, and classroom performance are greatly affected by their attitudes. The impact of primary teacher preparation programs on the values and beliefs held by future educators is the focus of this research. A standardized Attitude toward Teaching Scale was administered to a group of primary school teacher-to-bes at the beginning and end of a two-year teacher education program. With the use of descriptive and inferential statistics, the research used a pre-test-post-test strategy to examine how attitudes changed. Students’ views toward education were shown to be much improved after participating in pedagogical training, practical experiences, learning about child-centered pedagogies, and engaging in reflective practices as instructors. Professional dedication, effectiveness in the classroom, and awareness of students’ needs were all bolstered by the curriculum. Furthermore, the importance of mentorship, internships, and collaborative learning in developing good attitudes about work was emphasized in the qualitative comments. The research found that primary teacher education programs are very important for producing future teachers who are competent, motivated, and reflective because they help students develop positive attitudes about teaching. To further enhance teacher attitudes and preparation for the profession, recommendations include improving reflective practice components, increasing practical exposure, and incorporating technology-supported teaching.